Swap Pricing with Two-Sided Default Risk in a Rating-Based Model - Huge, Brian; Lando, David (Review of Finance, 1999)
Brian Huge, David Lando; Swap Pricing with Two-Sided Default Risk in a Rating-Based Model *, European Finance Review, Volume 3, Issue 3, 1 January 1999, Pa